THE FLOUTING OF THE CONVERSATIONAL MAXIMS BY OPERA VAN JAVA’S PLAYERS IN “HADIDIE DAN MAIMUN” EPISODE TRANS 7 - FIRMA, MOHAMMAD ADEN (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Cooperative Principle, Conversational Maxims, Flouting Maxims, Humor and Laughter Cooperative Principle that deals with conversational maxims is the rule that needs to be maintained during conversation. However, people realize they are not always supposed to be serious in having conversation. Sometimes, they break the Cooperative Principle by creating jokes. Therefore, to reveal this humor creations, this study uses “Hadidie dan Maimun” Opera Van Java’s episode as the subject of the study. There are three research problems in this study, namely: (1) what types of conversational maxims are flouted in causing laughter of the audiences in the episode “Hadidie dan Maimun” Opera Van Java Show Trans 7, (2) what are the intended meanings of maxims being flouted in the episode “Hadidie dan Maimun” Opera Van Java Show Trans 7, and (3) how can the flouting of the maxims cause humorous effect in the episode “Hadidie dan Maimun” Opera Van Java Show Trans 7.This study uses qualitative approach by using document analysis to identify the data. In this study, the writer found that all four maxims had been flouted by the players to cause laughter of the audiences. The flouting of the maxims could cause humorous effect was when the players had their particular intentions on their utterances. To cause humor, they flouted Maxim of Quality to avoid and conceal anger, play a fool, conceal enviousness and perform ridiculous action. They flouted Maxim of Quantity as a self-teasing, self-defense, and dejection. They flouted Maxim of Relation by word-playing, demonstrate selfmockery,self-defense, insensibility and foolishness. They flouted Maxim of Manner in making the utterances obscure by word-playing. The maxims which were flouted most were Maxim of Relation because they could easily cause humor by being irrelevant toward the topic of conversation. The maxims which were flouted least were Maxim of Quantity.There were also some factors encourage the players to flout the Maxims such as the different status as the player, relationship, behavior, emotion, unconsciousness, and the benefit of the language usage. In result, the writersuggests the next researcher to find out other theories of humor with the different subject of study such as Talk Show, Stand-Up Comedy Show, etc.